KEMAMPUAN LITERASI NUMERASI SISWA KELAS V SEKOLAH DASAR DALAM MENYELESAIKAN SOAL OPERASI HITUNG CAMPURAN BILANGAN CACAH - Shakira Daffa Dil; Riza Fatimah Zahrah; Geri Syahril Sidik (STKIP Subang, 2026)
Numeracy literacy is one of the fundamental competencies students must acquire in elementary mathematics learning, particularly on the topic of mixed arithmetic operations of whole numbers. This study aimed to describe the numeracy literacy ability of fifth-grade students, identify the difficulties they experienced, and analyze the factors causing those difficulties in solving mixed arithmetic operation problems. This research used a qualitative descriptive method involving 24 fifth-grade students of SDN 1 Gunungtanjung, six of whom were selected through purposive sampling as the main subjects, together with the classroom teacher as a supporting informant. Data were collected through tests, observation, interviews, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldana, covering data reduction, data display, and conclusion drawing with verification. The results showed that students' numeracy literacy ability varied, with 45.83% of students in the high category, 33.33% in the moderate category, and 20.83% in the low category. Students still experienced difficulties in understanding word problems, determining solution strategies, performing mixed arithmetic operations in the correct order, and communicating final answers according to the context of the problem. These difficulties were caused by limited understanding of the problem text, an unstable mastery of mixed operation concepts, low attention and engagement during learning, and insufficient practice, with reading ability also emerging as a contributing factor for one student. These findings imply the need for more varied and gradual learning strategies to strengthen students' numeracy literacy.